STRUCTURAL ANALYSIS OF VAN BODY-IN-WHITE - LI CaiXia (Jixie qiangdu)
During the lightweight process of automobile,the body structure strength cannot meet the design requirement,which leads to components failure. In this paper,strength analysis of van body-in-white was done under six kinds of working conditions: fully load,1g braking,0. 8g turning,150 mm right front wheel rising,150 mm left rear wheel rising,150 m both right front wheel and left rear wheelrising. Then the stress distribution of vehicle under various working conditions was got and the danger zones were confirmed. Finally,strain and stress tests under fully load were conducted to confirm the simulation results,which can help us with the structural design of van body-in-white.